Kajian Penggunaan Antibiotik pada Terapi Empiris dengan Hasil Terapi Di Ruang Icu RSUD "X" Periode 2015Universitas Muhammadiyah Surakarta - Sari, Diah Putri Permata; , Drs. Suharsono, Sp FRS., Apt; , Dr. dr. EM Sutrisna, M. Kes (2017)
Antibiotics are needed to treat infectious diseases which is caused by bacteria. The purpose of this study is to determine the use of empirical antibiotic therapy with the results of patients in the ICU Hospital's "X" period of 2015. This research was an observational research with descriptive design and the data was taken by retrospective, with sampling technique was purposive sampling. The results show that the empirical antibiotic common used in the ICU Hospital's "X" period of 2015 which antibiotic Ceftriaxone amounted to 40,85% with the 200 mg dose, frequency of 1x1 with the route iv. Results of therapeutic antibiotics in empirical therapy in the ICU Hospital's "X" period of 2015: recover as much as 34.57%; at their own request (return or relocate at the hospital) as much as 3.70%; and died as much as 61.73%.